Leadership Function in Technical Education Institutions - Wakhlu, O. N. (Journal of Engineering Education Transformations, 1990)
The aim of this paper is to highlight the role of leadership function in technical education institutions for their better performance. In a democratic society, leadership responsibility is widespread amongst the personnel, and effective leadership at all levels is the sine qua non of an efficient and well managed institution.